Pemahaman Perspektif Sosial, Penalaran Moral dan Prososial, serta Pengaruh Teman Sebaya pada Siswa Sekolah Dasar - Puri Selfi Cholifah (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2017)
Education that can be seen from psychosocial perspective is an attempt to develop human capacity through interpersonal relationship in society or family. Furthermore, a school plays important role in developing social and moral skills and cognitions, as an integral part of student’s development tasks, including its positive and negative impacts of peer relationship that occurs in elementary context. Consequently, it is needed an integral comprehension related to development tasks in specific context in order to detect, prevent, or cure the problems of the students. This paper explores a conceptual analysis of several context related to social perspective, moral and prosocial reasoning that divided into two characteristics, and impact of peer relationships both in positive and negative and its concept as social agent.